IMPLEMENTASI PEMBELAJARAN DARING BAGI ANAK DENGAN GANGGUAN SPEKTRUM AUTISTIK DI SD - Asep Asep; ana nurhasanah; Indina Tarjiah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This study aims to describe the implementation of online learning for autistic children at SD Negeri Kadudampit, Pandeglang. This research was conducted through narrative method with interview techniques. The subjects of this study were fifth grade teachers at SD Negeri Kadudampit 3, Pandeglang Regency, Banten. Data were collected through interviews and documentation. The results showed that the implementation of online learning for children with autism was still ineffective due to inadequate facilities and infrastructure. Learning process refers to the principles of 1) structured; 2) patterned; 3) programmed; and 4) consistent. The implementation of structured learning covers all four principles mentioned. The teachers can do some efforts to overcome these barriers by lowering knowledge indicators into lower levels and taking some individual approaches.Keywords: Online learning, Autistic Children, Individual Approach